Critiquing Scientific Articles and Popular Articles from the Perspective of Educational Curriculum Management - Nuphanudin; Maulidiyah, Hikmatul; ilmiah, Agniyatul; Najwa, Febriana Azzimatun (The Indonesian Institute of Science and Technology Research, 2026)
The ability to critically analyze scientific and popular articles is an essential part of critical literacy that supports the quality of higher education. This study aims to examine how curriculum management accommodates the development of critical article analysis skills among students. A qualitative descriptive study with a case study approach was employed, involving curriculum document analysis, interviews with lecturers and students, and classroom observations. The results reveal that the development of critical skills is more focused on scientific articles, while popular articles receive less attention in the curriculum. These findings emphasize the need to integrate the critical analysis of both types of articles simultaneously within curriculum management to enhance students’ critical literacy. This study contributes a conceptual model for integrating text criticism into higher education curriculum design.